Peran Pemerintah Desa Dalam Pengendalian dan Pengelolaan Lingkungan Hidup di Desa Ulumahuam - Dewi Dokate Boang Manalu; Rika Nurmitha; Windy Mariska Suryani Siregar; Yungki Akbar; Yani Lubis (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Environmental protection is very necessary because the population of the earth is increasing every year. The Village Government is absolutely responsible for what has been done to the community to fulfill its duties, authorities and obligations as regulated in laws and regulations, including in terms of providing a good living environment. This study focuses on finding out how the role of the village government in controlling and managing the environment in Ulumahuam Village is. This study used qualitative research methods. The data collection process was carried out by observing and asking questions. The results show that the Ulumahuam Village government controls and manages the environment by strengthening community harmony through mutual cooperation activities. In addition, the village government also utilizes existing natural resources to be managed into tourist attractions so that it can move the economy of local residents. Keyword: The Role of the Village Government, Monitoring and Management, Environment.